Bacteriophage T4 DNA topoisomerase is the target of antitumor agent 4'-(9-acridinylamino)methanesulfon-m-anisidide (m-AMSA) in T4-infected Escherichia coli. - Huff, A C (1989)
The mammalian type II DNA topoisomerase has been proposed to be the intracellular target of a variety of antitumor agents, including m-AMSA [4'-(9-acridinylamino)-methanesulfon-m-anisidide]. Because the bacteriophage T4-encoded topoisomerase resembles the mammalian enzyme, we are using T4 as a simple model system to investigate the mechanism of action of m-AMSA. A mutation that renders T4 growth m-AMSA-resistant is closely linked to an amber mutation in T4 gene 39, which encodes one of the topoisomerase subunits. In addition, the gene 39 subunit from the m-AMSA-resistant mutant phage has an altered net charge, strongly indicating that the drug-resistance mutation is within gene 39. Topoisomerase purified from mutant phage-infected Escherichia coli exhibits drug-insensitive DNA relaxation and DNA cleavage activities. Because a single mutation results in both drug-resistant phage growth and a drug-insensitive viral topoisomerase, we conclude that the T4-encoded type II DNA topoisomerase is the physiological target of m-AMSA in phage-infected E. coli.